(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Monitoring water quality and quantity is essential for sustainable water resource management. This study investigates changes in the extent and water quality of Kaptai Lake using remote sensing, field measurements, and laboratory analysis. Analysis of Landsat TM/OLI images from 1989, 2000, 2010, and 2021 shows that the lake’s water extent ranges from 380 km² (in 2010) to 435 km² (in 2021), with an average of 407.5 km². The extent of water decreased by approximately 3% from 1989 to 2010 and increased by about 5% from 2010 to 2021 due to changing rainfall patterns, dam operations, sedimentation, and land use changes. Seasonal variations in chlorophyll-a concentration and turbidity, analyzed using Sentinel 2B images from 2022 and 2023, indicate mesotrophic to eutrophic conditions and higher turbidity in post-monsoon. The study found that nutrient enrichment from untreated sewage, agricultural runoff, and algal growth affect chlorophyll-a levels, while development activities, excessive rainfall, and sedimentation influence turbidity. Linear regression analyses show strong positive correlation between field obtained and image derived values both for chlorophyll-a (R2 0.621) and turbidity (R2 0.698). Physico-chemical parameters such as pH, EC and temperature have been measured in the field and hydrochemical parameters including, cations and anions have been measured by laboratory analysis to assess the contemporary water quality status. The average values for pH, EC and temperature are 7.55, 119.85 µS/cm and 22.17 °C respectively. The cationic dominance in the studied segment of the Lake is in the order of Ca2+ > Na2+ > Mg2+>K+ > Fe2+ >Mn2+. On the other hand, the anions are in the order of HCO3- > SO42- > Cl- > NO3-. All the physico-chemical parameters of the lake water fall within the Bangladesh Drinking Water Limit (BDWL) and are not linked to chlorophyll-a and turbidity variations. The findings of this study can help mitigate the deterioration of Kaptai Lake by addressing water quality and extent issues, promoting effective and sustainable lake management strategies. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 121-139